Histopathological changes in testis of the swordtail fish, Xiphophorus helleri (Pisces: Poecilidae) exposed to deltamethrin - (:unkn) unknown (My University, 2012)
This experiment was done in order to investigate the effects of deltamethrin on the testis tissue of swordtail fish. In this study, 90 swordtail fishes were examined in 2 experimental groups. Low (0.2 ppm) and high (0.4 ppm) sublethal doses of deltamethrin were added into the habitat of fishes which were sacrified after 72 hours. Tissues were dissected out, fixed in Bouin's fixative, stained with Hematoksilen & Eosin, and examined using light microscopy. It is observed that a low dose of deltamethrin in the testis of swordtail does not generate structural defect characteristics. Depending on increasing doses, numbers of mature sperm were significantly reduced, and degenerative changes in seminiferous tubules were observed. In conclusion, we can say that pesticide contamination affects the quality of sperm significantly. © by PSP.
Keywords: Deltamethrin; Histopathology; Swordtail fish; Testis